(untitled) (World Bulletin of Social Sciences, 2022)
Strengthening health, raising physical maturity, enhancing body function, and honing physical abilities are four problems that physical fitness addresses. Physical training is split into two categories from a pedagogical perspective: general training and specialized training. The goal of general physical fitness is to support the aforementioned health and heighten physical maturity, whereas the goal of special physical fitness is to provide the body with the main structural support necessary to develop its functional capacity and train its physical abilities. The selection and beginning training of young volleyball players from outdoor folk games is discussed in this article along with feedback on the process